The New Rural School in Upper Galilee (Eretz Israel) at the Beginning of the 20th Century - Yuval Dror (Journal of Research in Rural Education, 1993)
This article proposes amodel for ruraleducationbased on the idea that history canassist in thedetermination of contemporary educational policy. A case study of a rural school in Upper Galilee in Eretz Israel at the beginning of this century is the sourceof a comprehensive model. The modelcombines desirable characteristics of rural education organizedin four innovative educational paradigms: educationfor work , community education,social-ideological education,and thefourth element on which theothers depend, the curricular autonomy of the teacher and school in remote rural areas. The result complements the partial and administrative definitions that exist at present.